Impact of the use of informatic technology, to improve management of adult teaching, in Lima - Peru, 2019 - Farfán Cuya, Amaury Aldo (2020)
In times where job training, as a mechanism to improve skills and increase the chances of improving economically, these trainings are one of the main concerns in the adult population, in this work a population of adult workers was evaluated, that work in a state institution that have policies related to the constant training of its staff, for the constant promotion of its employees and the different changes of employment and tasks entrusted, the management of education is of vitalimportance to measure the indicators from where it is measured if the policies are giving good results, two widely used mechanisms were evaluated, the intervention consists of a one-month face-to-face training versus virtual training for the same period of time, evaluating both face-to-face and extra-curricular hours, in both solutions, the results demonstrate and allows b Good hope in being applied in other groups of workers is the solution with the use of computer technologies, taking advantage of the resources provided by these educational platforms, in relation to traditional methods where extra-curricular activities depend mostly on Concern and dedication of student. The use of curricular activities indicates a 90% use with the use of computer technologies compared to 55% of the face-to-face method, in the use of face-to-face classes as they are considered hours worked and paid by the employer to register 98 % compared to 95% in the modality using educational technology.